Radical monocationic guanidino-functionalized aromatic compounds (GFAs) as bridging ligands in dinuclear metal acetate complexes: synthesis, electronic structure, and magnetic coupling - Eberle, Benjamin; Damjanović, Marko; Enders, Markus; Leingang, Simone; Pfisterer, Jessica; Krämer, Christoph; Hübner, Olaf; Kaifer, Elisabeth; Himmel, Hans-Jörg (Inorganic chemistry, 2016)
In this work, the oxidation of several new dinuclear metal (M) acetate complexes of the redox-active guanidino-functionalized aromatic compound (GFA) 1,2,4,5-tetrakis(tetramethylguanidino)benzene (1) was studied. The complexes [1{M(OAc)2}2] (M = Ni or Pd) were oxidized to the radical monocationic complexes [1{M(OAc)2}2]+•. From CV (cyclic voltammetry) measurements, the Gibbs free enthalpy for disproportionation of [1{M(OAc)2}2]+• into [1{M(OAc)2}2] and [1{M(OAc)2}2]2+ could be estimated to be roughly +20 kJ mol-1 in CH2Cl2 solution. A characteristic feature of the [1{M(OAc)2}2]+• complexes is the presence of intense metal-ligand charge-transfer bands in the electronic absorption spectra. The complex [1{Ni(OAc)2}2]+• combines three paramagnetic centers with four metal-centered unpaired electrons and a ligand centered π-radical and exhibits a sextet electronic ground state. Spin distribution of the Ni complexes was evaluated by paramagnetic 1H and 13C NMR and was correlated with calculations. The strong ferromagnetic metal-ligand magnetic coupling was studied in the solid state by magnetometric (SQUID) measurements and by quantum chemical (DFT) calculations. The temperature dependence of the paramagnetic NMR shift was used for the evaluation of the magnetic coupling between the Ni centers and the π-radical in solution.
Gesehen am 30.04.2020